Sobre um “Monstro bicorpóreo Eborense do século XVIII” - Luís Ceríaco (Midas: Museus e Estudos Interdisciplinares)
A document preserved in the Public Library of Évora states that a female "double-bodied monster" with a cleft lip was born in the city in 1778, which was dissected and drawn in the city and finally sent to the Royal Museum of Natural History of Ajuda, Lisbon. Unaware of its current location, we proceeded with research in order to find it. The specimen was found in October 2011, in the teratology collection at the Museum of Medicine of the Faculty of Medicine, University of Lisbon, but had not been identified as such. The journey of this specimen is quite similar to other eighteenth century Portuguese "monsters", showing the evolution of museums and science itself. This specimen constitutes one of the oldest Portuguese teratology specimens and is an important historical and scientific specimen.